2015
DOI: 10.2144/000114290
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Modification to the Luminometric Methylation Assay to Control for the Effects of DNA Fragmentation

Abstract: Variations in DNA methylation have been implicated in a number of disorders. Changes in global DNA methylation levels have long been associated with various types of cancer. One of the recently described methods for determining global DNA methylation levels is the LUminometric Methylation Assay (LUMA), which utilizes methylation sensitive and insensitive restriction endonucleases and pyrosequencing technology for quantification. Here we provide evidence suggesting that the global methylation level reported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, LUMA assays may differ from high-pressure liquid chromatography because the success of a DNA-digestion-based assay is dependent on the integrity of the DNA. 34 Additionally, epigenetic measures may be affected by differences in cell-type distribution of samples or tissue types assayed across studies which are not adjusted for in most studies. 21 One of the strengths of the current study was the evaluation of sensitive windows of micronutrient exposure and %5mC and % 5hmC at multiple time points to assess persistence of associations in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LUMA assays may differ from high-pressure liquid chromatography because the success of a DNA-digestion-based assay is dependent on the integrity of the DNA. 34 Additionally, epigenetic measures may be affected by differences in cell-type distribution of samples or tissue types assayed across studies which are not adjusted for in most studies. 21 One of the strengths of the current study was the evaluation of sensitive windows of micronutrient exposure and %5mC and % 5hmC at multiple time points to assess persistence of associations in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…While a daily intake of 200–320 μg folate was associated with a lower breast cancer risk, a daily intake of >400 μg significantly increased the risk 35 . Studies that focused on gene‐specific methylation, instead of global methylation, observed more consistent and reproducible findings 36 …”
Section: Role Of Biofactors In Cancer and Epigeneticsmentioning
confidence: 93%
“…Distinct methylation profiles of various repetitive DNA elements have been found among different tissues and pathological conditions. Furthermore, loss of DNA integrity in cancer may compromise the accuracy of global DNA methylation assay outcome [142]. Thus, using different global DNA methylation assays to evaluate the effect of folate status on DNA methylation could be the reason behind the reported inconsistent and irreproducible findings.…”
Section: Micronutrients and Dna Methylation And Their Impact On Camentioning
confidence: 99%